The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1136/bmjopen-2021-059540
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine plus personal protective equipment versus personal protective equipment alone for the prevention of laboratory-confirmed COVID-19 infections among healthcare workers: a multicentre, parallel-group randomised controlled trial from India

Abstract: ObjectivesTo determine whether hydroxychloroquine when used with personal protective equipment reduces the proportion of laboratory-confirmed COVID-19 among healthcare workers in comparison to the use of personal protective equipment alone.DesignMulticentre, parallel-group, open-label randomised trial. Enrolment started on 29 June 2020 and stopped on 4 February 2021. Participants randomised in HydrOxychloroquine Prophylaxis Evaluation were followed for 6 months.Setting9 hospitals across India.ParticipantsHealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Since HCQ has proven to be able to prevent SARS-CoV-2 infection in vitro,31 32 a number of clinical trials and observational studies embarked on evaluating HCQ as prophylaxis to contain SARS-CoV-2 in the human body. Most of these studies reported non-significant associations between HCQ prophylaxis and reduced SARS-CoV-2 infection rate,15 19 21 33–50 while only a few reported HCQ prophylaxis could significantly decrease SARS-CoV-2 infection rate 51–59. Our findings of significant association between PrEP use of HCQ and reduced risk of SARS-CoV-2 infection in clinical trials are consistent with another meta-analysis of cohort studies among high-risk HCWs performed by Stricker and Fesler 60.…”
Section: Discussionsupporting
confidence: 87%
“…Since HCQ has proven to be able to prevent SARS-CoV-2 infection in vitro,31 32 a number of clinical trials and observational studies embarked on evaluating HCQ as prophylaxis to contain SARS-CoV-2 in the human body. Most of these studies reported non-significant associations between HCQ prophylaxis and reduced SARS-CoV-2 infection rate,15 19 21 33–50 while only a few reported HCQ prophylaxis could significantly decrease SARS-CoV-2 infection rate 51–59. Our findings of significant association between PrEP use of HCQ and reduced risk of SARS-CoV-2 infection in clinical trials are consistent with another meta-analysis of cohort studies among high-risk HCWs performed by Stricker and Fesler 60.…”
Section: Discussionsupporting
confidence: 87%
“…We don't have an effective pharmacological preventive therapy for a COVID-19 outbreak even though it has been more than a two years since the pandemic begun. Hydroxychloroquine was recommended by the Indian Council of Medical Research (ICMR) as a pre-exposure prophylaxis without substantial clinical studies and was found to be ineffective [ 4 , 5 ]. Remdesivir has shown benefit in reduction of disease progression by 87% in high risk patients if given within 3–5 days of symptom onset [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remdesivir has shown benefit in reduction of disease progression by 87% in high risk patients if given within 3–5 days of symptom onset [ 6 ]. Non-pharmacological measures like wearing a mask, social distancing and hand hygiene proved to be useful in controlling the spread of infection [ 5 ]. COVID-19 vaccination has proved beneficial in reducing hospitalization and mortality from COVID-19 across various countries [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tummino et al [3] established that the threshold concentration for inducing phospholipidosis in cultured cells is correlated to the antiviral activity. Several drugs from the list, including chloroquine, hydroxycholoquine and amiodarone, have been investigated in clinical trials for COVID-19 treatment or prevention, but without success [2,3,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%